ASUPAN BUAH SAYUR, ASUPAN MAKANAN TINGGI NATRIUM, DAN HIPERTENSI PADA REMAJA KECAMATAN CIPARAY KABUPATEN BANDUNG (Jurnal Kesehatan Siliwangi, 2022)
Eating behavior is one of the risk factors for increasing blood pressure in adolescence. Behavior that is thought to cause an increase in blood pressure in adolescents is the consumption of fruit and vegetables and high sodium intake. The purpose of this study was to determine the description of fruit and vegetable intake, high sodium intake, and hypertension in adolescents in Babakan Village, Ciparay District, Bandung Regency. The research design used was cross sectional with 36 respondents. Data were collected primary, data on consumption of fruit and vegetables intake and high sodium intake were used semiquantitative food frequency questionnaire (SFFQ); Blood pressure data was collected based on the results of measurements using a digital blood pressure meter. The results of the study were analyzed descriptively, it was found that the respondents who had hypertension were 75.0%; 50.0% of respondents consuming less fruit and vegetables: 50.0% of respondents consuming high-sodium foods. Bivariate descriptive analysis showed that 77.8% of respondents with hypertension had less intake of fruit and vegetables; 77.8% of respondents with hypertension have a high intake of high sodium foods. It is recommended to increase cooperation with the puskesmas and other parties to provide youth education related to the consumption of fruit and vegetables as an effort to prevent non-communicable diseases